A review of next-generation immuno-oncology agents for cancer therapy: recent dictation shifts in cancer immunotherapy - Ratu, Tabassum (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2023.